Arabic Language Learning Using The Al-Arobiyah Baina Yadaik Book for First Grade Junior High School Students at Bina Madani Islamic Boarding School Bogor: English - Arif Padriansyah; Fachrur Razi Amir; Desky Halim Sudjani; Siti Khumairotuzzahra (Tatsqifiy: Jurnal Pendidikan Bahasa Arab, 2025)
Abstract: This research aims to describe how Arabic language learning for first grade Junior High School Students at Bina Madani Islamic Boarding School in Bogor. The study uses a qualitative approach with a phenomenological type. Data collection techniques include observation, interviews, and documentation. The collected data is analyzed following the steps outlined by Miles, and Huberman (2014), which involve data collection, data condensation, data presentation, and conclusion drawing. The results of this study have found three importans points. First, the Arabic language learning curriculum used at Bina Madani Islamic Boarding School Bogor City employs the book Al-Arobiyah Baina Yadaik. The learning steps taken by the Arabic language teachers for the first grade junior high school students at Bina Madani Islamic Boarding School in Bogor are in accordance with the learning implementation procedures. The evaluation of learning using the book Al-Arobiyah Baina Yadaik is carried out as a material for improvement and enhancement of learning and its implementation. The evaluation is conducted with two types of tests, namely written tests and memorization tests